Konstitusional Pasal Penghinaan Terhadap Presiden dan/atau Wakil Presiden Dalam Perspektif Kebebasan Berpendapat bagi Warga Negara (Telaah Atas Pasal 217-220 Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana) - Sholeha, Faridatus; Musfianawati, Musfianawati; Hoiru Nail, Muhammad (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2023)
The Constitutional Court decision No.013-022/PUU-IV/2006 issued in 2006, it was stated that the article on insulting the President contained in Article 134, Article 136 and Article 137 of the Criminal Code no longer had binding legal force. The Constitutional Court stated that in its ratio decidendi regarding the abolition of the article on insulting the President and/or Vice President, namely with several considerations: 1) The Criminal Code is a legacy of Dutch colonialism. 2) Give rise to legal uncertainty (rechtsonzekerheid) and the principle of equality before the law does not apply. 3) protection of human rights. The redaction of the article on insulting the President and/or Vice President as stated in Article 217-Article 218 of Law the Criminal Code is no different from the redaction of the article on insulting the President and/or Vice President which has been declared unconstitutional by the Constitutional Court. Minimize the occurrence of a judicial review in the next three years regarding the article regarding insulting the President and Vice President. So the restrictions on the article regarding insulting the President and Vice President can be regulated by equivalent legal regulations, such as government regulations as a matter of urgency in explaining the article.